Analisis User Experience pada Aplikasi Linkedln dengan Menggunakan Metode SUS - Febriani, Ria; Syafrianto, Syafrianto (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2025)
LinkedIn is one of the professional social media platforms that is widely used for job searching and building a digital personal image. Although its usage is quite extensive, there are still several obstacles in user experience, such as features that are not yet fully understandable and difficulties in understanding the application's usage flow, especially for new users. This situation is the reason LinkedIn was chosen as the research object to evaluate user usability. This research aims to assess the user experience of the Linkedin application using a descriptive quantitative approach and the System Usability Scale (SUS) instrument. Data were obtained from 110 active respondents of Linkedin users through the distribution of online questionnaires. The results of the validity and reliability tests indicate that all question items are valid and consistent. The average SUS score obtained is 62.85, which falls into the 'Marginal' category. which indicates that this application is rated reasonably well by users, but still requires improvements in some aspects to provide a better experience.